Increased germination and growth rates of pea and Zucchini seed by FSG plasma - Shohreh Khatami; Arash Ahmadinia (Journal of Theoretical and Applied Physics)
Abstract Recently, cold atmospheric plasma (CAP) with the unique bio-disinfection features is used in various fields of industry, medicine, and agriculture. The main objectives of this work were to design FSG plasma (a semi-automatic device) and investigate the effect of the cold plasma in the enhancement of the Pea and Zucchini seed germination. Plasma irradiation time was studied to obtain a proper condition for the germination enhancement of seeds. The growth rate was calculated by measuring length of root and stem and dry weight of plants treated by plasma. To investigate drought resistance of plants, all treated and untreated samples were kept in darkness without water for 48 h. From the experimental results, it could be confirmed both drought resistance and germination of seedlings increased after plasma was applied to seeds at 30 s, while seeds treated whiten 60 s showed a decrease in both germination rate and seedling growth.